Effects of isolated vitamin B6 supplementation on oxidative stress and heart function parameters in experimental hyperhomocysteinemia - Mendes, Roberta Hack; Candido, Georgia Orsi; Mostarda, Cristiano; Sirvente, Raquel; D’Almeida, Vânia; Ribeiro, Maria Flávia; Araújo, Alex Sander da Rosa; Salemi, Vera Maria Cury; Rigatto, Katya; Irigoyen, Maria Cláudia Costa; et al. (Clinical and Biomedical Research, 2017)
Introduction: The purpose of this study was to investigate the effects of isolated vitamin B6 (VB6) supplementation on experimental hyperhomocysteinemia (Hhe) induced by homocysteine thiolactone (HcyT). Methods: Fifteen male Wistar rats were divided into three groups according to their treatment. Animals received water and food ad libitum and an intragastric probe was used to administer water for 60 days (groups: CB6, HcyT, and HB6). On the 30th day of treatment, two groups were supplemented with VB6 in the drinking water (groups: CB6 and HB6). After 60 days of treatment, homocysteine (Hcy), cysteine, and hydrogen peroxide concentration, nuclear factor (erythroid-derived 2)-like 2 (NRF2) and glutathione S-transferase (GST) immunocontent, and superoxide dismutase (SOD), catalase (CAT), and GST activities were measured. Results: The HcyT group showed an increase in Hcy concentration (62%) in relation to the CB6 group. Additionally, GST immunocontent was enhanced (51%) in the HB6 group compared to the HcyT group. Also, SOD activity was lower (17%) in the HB6 group compared to the CB6 group, and CAT activity was higher in the HcyT group (53%) compared to the CB6 group. Ejection fraction (EF) was improved in the HB6 group compared to the HcyT group. E/A ratio was enhanced in the HB6 group compared to the CB6 group. Correlations were found between CAT activity with myocardial performance index (MPI) (r = 0.71; P = 0.06) and E/A ratio (r = 0.6; P = 0.01), and between EF and GST activity (r = 0.62; P = 0.02). Conclusions: These findings indicate that isolated VB6 supplementation may lead to the reduction of Hcy concentration and promotes additional benefits to oxidative stress and heart function parameters. Keywords: Homocysteine; oxidative stress; vitamin B6.